Pre-therapy Iodine-131 Uptake Value as a Prediction Method for Metastatic Lymph Node Status in Patients with Differentiated Thyroid Carcinoma - Ege Aktas, Gul; Soyluoglu Demir, Selin; Ustun, Funda; Sarikaya, Ali; Durmus Altun, Gulay (Current Medical Imaging, 2017)
Background: We hypothesized that postoperative lymph node status would affect I-131 uptake (RIU) due to pathophysiological behavior of benign and malign thyroidal tissue. This retrospective study was designed to assess whether RIU would predict the presence of lymph node metastasis (LNM). Methods: Data for differentiated thyroid cancer patients who received postoperative I-131 therapy at our institution between 2013 and 2016 were reviewed. Age, histopathology, TSH, Tg, anti-Tg, 2 and 24 hour RIU (2-24RIU), ultrasonography, I-131 dose, scans were reviewed. Patients were divided into groups according to lymph node status. The ΔRIU was calculated (ΔRIU=24RIU-2RIU) to define different metabolic behavior of I-131. Patients were grouped according to ΔRIU to assess the sensitivity, specificity, negative/positive predictive values, accuracy of ΔRIU predicting LNM. Results: 198 patients (38 males /160 females, age: 47±14 years) who received mean: 118±27 mCi I- 131 were enrolled in the study. There was no difference between ages, TSH level, 2RIU values and the I-131 therapy dose of patients with and without LNM. Tg, anti-Tg, 24RIU, ΔRIU values were higher in patients with LNM. Patients with ΔRIU≥1% had higher Tg values (mean±std: 16.63±46.53 vs. 6.70±31.18, p: 0.04). When ΔRIU≥1% was used for predicting LNM, sensitivity, specificity, positive, negative predictive values, diagnostic accuracy were, 66%, 72%, 64%, 74 %, and 70% respectively. Conclusion: RIU was evaluated to predict neck LN status in this study. The sensitivity and specificity were comparable with modalities which are commonly used for determination of LNM. In light of the results of this study, when a pre-therapy RIU increase in time is observed, carrying out further investigation protocols for LNM, would contribute to pre-therapy staging.
Keywords: lymph node metastasis